Status and Trends in Pyroprocessing of Spent Nuclear Fuels. (International Atomic Energy Agency, 2021)
"The importance of recycling the spent nuclear fuel through partitioning processes has been recognized worldwide for increasing and sustaining nuclear energy. Therefore, the development of advanced partitioning processes, based either on hydrometallurgical or on pyrometallurgical technologies, has received an increasing interest in recent years. Moving towards industrial demonstration, partitioning processes are applied for the separation of actinides, including minor actinides, not only to reduce the burden of high level waste to be disposed of, in terms of heat-load and radiotoxicity, but also to improve the efficiency of the resources' utilization. Furthermore, in the case of Molten Salt Reactors, whose fuel cycle is primary based on pyrochemical processes, there is a need for strengthening pyrometallurgical technologies. This publication reviews the status and trends in the development of pyrometallurgical processes and technologies for processing spent nuclear fuel and identifies gap areas requiring further development."--Publisher's description.
"August 2021"--Title page verso.
Keywords: Spent reactor fuels.; Reactor fuel reprocessing.; Nuclear fuels -- Recycling.; elektronické knihy; electronic books